2014
DOI: 10.1186/preaccept-3619132851279195
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating immunologic mechanisms of PROSTVAC cancer immunotherapy

Abstract: Background: PROSTVAC W , an active immunotherapy currently studied for the treatment of metastatic castration-resistant prostate cancer (mCRPC), consists of a heterologous prime-boost regimen with two different poxvirus-based vectors to provoke productive immune responses against prostate specific antigen (PSA) as the target tumor antigen. A Phase 2 study of PROSTVAC immunotherapy showed significantly improved median overall survival by 8.5 months and is currently being validated in a global Phase 3 study (PRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This utilizes viral vectors derived from fowl pox and the booster vaccination, which both code for the same tumor-associated antigens. 30 This strategy was evaluated in patients with localized PCa with PSA recurrence after radical treatment. 31 A positive trend with prolongation of PSA-free survival was observed in the patient cohort that received a single injection of PROSTVAC-V followed by multiple injections of PROSTVAC-F. 31 Meanwhile, a study by Hodge et al showed much greater T-cell activation when a triad of costimulatory molecules (TRICOM) – leukocyte function-associated antigen-3 (LFA-3), B7.1, and intercellular adhesion molecule-1(ICAM-1) – are used in conjunction with PSA.…”
Section: Vaccinesmentioning
confidence: 99%
“…This utilizes viral vectors derived from fowl pox and the booster vaccination, which both code for the same tumor-associated antigens. 30 This strategy was evaluated in patients with localized PCa with PSA recurrence after radical treatment. 31 A positive trend with prolongation of PSA-free survival was observed in the patient cohort that received a single injection of PROSTVAC-V followed by multiple injections of PROSTVAC-F. 31 Meanwhile, a study by Hodge et al showed much greater T-cell activation when a triad of costimulatory molecules (TRICOM) – leukocyte function-associated antigen-3 (LFA-3), B7.1, and intercellular adhesion molecule-1(ICAM-1) – are used in conjunction with PSA.…”
Section: Vaccinesmentioning
confidence: 99%
“…The scientific rationale behind this vaccine is that the vaccinia vector acts as a single dose immunogenic factor, eliciting a strong immune response both against PSA and the viral protein, leading to the destruction of PSA-positive tumor cells and subsequently to the release of a wider range of TAAs (antigen spreading) that stimulate additional pro-inflammatory signals and additional tumor-specific T cell immune responses [109,125,126]. Under the same rationale, the fowlpox vector, transduced to code for the same TAA (PSA), is used for subsequent booster vaccinations in order to bypass the problem of the vaccinia virus vector being neutralized by the host immune system, as the former (PROSTVAC-F) is able to penetrate APCs without www.videleaf.com invoking the production of high volumes of neutralizing antibodies [62,127,128].…”
Section: Vector-based Vaccinesmentioning
confidence: 99%
“…Undoubtedly, the characterization of humoral and cellular immune responses against portions of viral proteins that are relevant for oncogenic activities, such as the p53‐binding regions of polyomaviruses LTag, could unravel the ways BKPyV becomes one of the major protagonists in PCa immunoediting, controlling cancer immune surveillance, and strengthening tumor immune escape. Therefore, further investigation of the systemic adaptive immune response to BKPyV LTag could clarify its role as a key target of cancer immune surveillance, which might also lead to an LTag‐targeted therapy, as already set by using target proteins such as the prostate‐specific antigen or the prostatic acid phosphatase for antigen‐specific immunotherapy .…”
Section: Bkpyv Ltag Exerts Tolerogenic Signatures In Pcamentioning
confidence: 99%